Les Audits Des Programmes ILDH : Les Balises D’une Évaluation Des Politiques Publiques Au Maroc - Mohammed Belga; Anass Kihli (European Scientific Journal, ESJ, 2017)
Policy assessment in Morocco is a recent method to measure the performance of public budget. It is considred as a new form of control of the effictiveness and efficiency of goverment expenditure. However, polemics have intensified about the content and the method of this new practice of control. The conception of an institutional framework of evaluation of public policy evaluation, has stood up to the multiplicity of its stakeholders. The double identity of the evaluative approach, proclaimed by public administration and parliament, made the definition of this practice problematic. Recently, The initiation of the ILDH programmes performance audit recently, has given gave a new path to follow, so as to get to the reality of the goverment evaluative action in Morocco.